2016
DOI: 10.1212/wnl.0000000000003321
|View full text |Cite
|
Sign up to set email alerts
|

Increasing atrial fibrillation prevalence in acute ischemic stroke and TIA

Abstract: Objective: To evaluate trends in atrial fibrillation (AF) prevalence in acute ischemic stroke (AIS) and TIA in the United States.Methods: We used the Nationwide Inpatient Sample to retrospectively compute weighted prevalence of AF in AIS (n 5 4,355,140) and TIA (n 5 1,816,459) patients admitted to US hospitals from 2004 to 2013. Multivariate-adjusted models were used to evaluate the association of AF with clinical factors, mortality, length of stay, and cost.Results: From 2004 to 2013, AF prevalence increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 22 publications
5
35
2
4
Order By: Relevance
“…This quantitative difference might lie in a higher severity of liver disease in our study, namely ESLD or decompensated cirrhosis. It has been previously well established that age, sex, race, income and insurance differences exist in AF prevalence in the general population or specific conditions like acute ischaemic stroke and end‐stage chronic obstructive pulmonary disease . Consistent with other studies, we found that advancing age, male, white race, higher income and Medicare insurance were related to increased AF occurrence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This quantitative difference might lie in a higher severity of liver disease in our study, namely ESLD or decompensated cirrhosis. It has been previously well established that age, sex, race, income and insurance differences exist in AF prevalence in the general population or specific conditions like acute ischaemic stroke and end‐stage chronic obstructive pulmonary disease . Consistent with other studies, we found that advancing age, male, white race, higher income and Medicare insurance were related to increased AF occurrence.…”
Section: Discussionsupporting
confidence: 90%
“…It has been previously well established that age, sex, race, income and insurance differences exist in AF prevalence in the general population or specific conditions like acute ischaemic stroke and end-stage chronic obstructive pulmonary disease. [33][34][35] Consistent with other studies, 17,19 we found that advancing age, male, white race, higher income and Medicare insurance were related to increased AF occurrence. More studies regarding these disparities are needed to provide further explanation.…”
Section: Discussionsupporting
confidence: 90%
“…AF currently affects over 5 million Americans, and this prevalence continues to increase . AF preferentially affects older adults (>70 years of age) and is a major risk factor for cardioembolic stroke . AF increases stroke‐risk 5‐fold, and 20% of all ischemic strokes present with AF .…”
Section: Introductionmentioning
confidence: 99%
“…AF preferentially affects older adults (>70 years of age) and is a major risk factor for cardioembolic stroke . AF increases stroke‐risk 5‐fold, and 20% of all ischemic strokes present with AF . For adults reaching age 40, the risk of developing AF during their lifetime is approximately 1 in 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing incidence and prevalence of stroke and AF itself is related to the aging of population [6]. It is entrenched that the incidences of AF among patients with IS are surging rapidly and thus results in higher general fatality as well as particularly higher stroke mortality rates [7,8]. Additionally, AF boosts health care and hospitalization expenditures, the usage of medical resources as well as the general economic burden which in itself is considerably weightful for stroke patients [9,10].…”
Section: Introductionmentioning
confidence: 99%